ANALISIS KEADILAN DALAM PEMBATALAN AKTA PERJANJIAN PENGIKATAN JUAL BELI HAK ATAS TANAH AKIBAT WANPRESTASI DALAM PUTUSAN PENGADILAN NEGERI DEPOK NOMOR 119/ PDT.G/ 2017/PN. DPK. - Ani Anggreni; Gunawan Djajaputra (Jurnal Hukum Adigama, 2021)
The Land Sale and Purchase Binding Agreement is a legal act that precedes the transfer of land rights which is binding, giving rise to the rights and obligations of the parties making it. In its implementation, sometimes one of the parties does not carry out its obligations, resulting in legal disputes in court, and court judges do not always give fair decisions. The problem in this research is how the value of justice in the cancellation of the agreement deed of sale and purchase of land rights due to default in the Depok District Court Decision Number 119 / PDT.G / 2017 / PN.Dpk? The results showed that the value of justice in the cancellation of the Deed of Sale and Purchase Agreement of land rights due to default in the decision of the Depok District Court Number 119 / PDT.G / 2017 / PN.Dpk did not occur. This is because the Depok District Court Judge mistakenly interpreted the default between the default and the act against the law, especially in relation to claims for compensation, because in the default lawsuit they could not demand return to their original state, but rather the calculation of compensation that was actually experienced by Ade Triana as the Plaintiff.